1992
DOI: 10.1002/glia.440060205
|View full text |Cite
|
Sign up to set email alerts
|

Expression of adrenergic receptors in individual astrocytes and motor neurons isolated from the adult rat brain

Abstract: Attempts to show the distribution of adrenergic receptors (ARs) in autoradiographs of a brainstem motor nucleus following elimination of motor neurons yielded the unexpected result of an increase in beta-AR density. This increase was related to the gliosis accompanying the motor neuron degeneration. To determine the cells on which the AR subtypes were located, we dissociated cells from various regions of the adult rat brain and subsequently identified astrocytes by glial fibrillary acidic protein (GFAP) immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…Astrocytes express ␣ and ␤ adrenergic receptor subtypes both in culture 36 and in situ. 37 ␤ receptors in mammalian brain are localized not only on neuronal membranes, but also on astrocytes. 36 Astrocytes have the ability to rapidly change their shape in response to changes in their chemical and cellular environment.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes express ␣ and ␤ adrenergic receptor subtypes both in culture 36 and in situ. 37 ␤ receptors in mammalian brain are localized not only on neuronal membranes, but also on astrocytes. 36 Astrocytes have the ability to rapidly change their shape in response to changes in their chemical and cellular environment.…”
Section: Discussionmentioning
confidence: 99%
“…17). However, in addition to being expressed in pre-and postsynaptic compartments of neurons, βARs are also found in other cell types, particularly in astrocytes (18)(19)(20)(21). More specifically, it has been suggested that β 2 ARs in the nervous system are expressed predominantly in glia (18,(21)(22)(23), whereas β 1 ARs are found primarily in neurons, at synaptic junctions (18,22,23).…”
mentioning
confidence: 99%
“…A high density of β-adrenergic receptors has also been demonstrated in the trigeminal motor nucleus, where β 2 -adrenergic receptors dominate [170]. After neuronal damage there is an increase in β-adrenergic receptor expression on astrocytes, with the greater proportional increase occurring in β 1 -adrenergic receptors.…”
Section: Intact Cnsmentioning
confidence: 93%
“…Later studies, using an antibody specifically to the C-terminal tail of the β 2 -adrenergic receptor (but recognizing both β 1 -and β 2 -adrenergic receptors) showed in visual cortex a predominant localization of the receptor on small astrocytic processes contacting catecholaminergic axon terminals [162][163]. Pronounced expression of β-adrenergic receptors has also been demonstrated by aid of the receptor ligand [ 125 I]iodocyanopindolol in both cerebral cortex, striatum and cerebellum, with the highest receptor density on cerebellar astrocytes [164]. In the kitten visual cortex close to one half of all β-adrenergic receptors were found on astrocytes [165].…”
Section: Intact Cnsmentioning
confidence: 98%
See 1 more Smart Citation